2005
DOI: 10.1111/j.1423-0410.2005.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

First year donation patterns predict long‐term commitment for first‐time donors

Abstract: Strategies aimed at encouraging current donors to donate more frequently during the first year may help to establish a regular donation behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
174
6
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(206 citation statements)
references
References 24 publications
18
174
6
8
Order By: Relevance
“…(6,8,9) Ownby et al (6) extended these findings showing that the time to the next return is strongly conditioned by the average period between previous returns. This, in the opinion of these authors, is an aspect that suggests that donors should be encouraged to return as soon as they meet the eligibility criteria for blood donation.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…(6,8,9) Ownby et al (6) extended these findings showing that the time to the next return is strongly conditioned by the average period between previous returns. This, in the opinion of these authors, is an aspect that suggests that donors should be encouraged to return as soon as they meet the eligibility criteria for blood donation.…”
Section: Discussionsupporting
confidence: 60%
“…Although an effort is needed to win over first-time blood donors, most strategies are systematically developed to encourage donors to return to donate more regularly . (6,(8)(9)(10)(11) Hence, specific subgroups need to be identified as there are differences in behavior of first-time, first-return and regular donors. (8) Schreiber et al (8) believe it is essential to focus on repeat donors with a history of regular donations, who would potentially be more responsive, thereby increasing the effectiveness of recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The number and the return rate of repeat donors were found to be an important issue. 12,23,[26][27][28] A study in Australia showed that if the donor return rate decreased from 88% to 85% over a two-year period, the number of first-time donors would be increased to 33%. 22 A previous study showed that a higher donor return rate was influenced by having information about patients' needs, having good experiences with previous donations and receiving assurance from the blood center.…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment of repeat donors is easier because of better cooperation 11 and fewer donor reactions. 12 Moreover, the cost-benefit ratio of repeat donation is better, and these donors require less education to be convinced to return. 13 To improve blood safety, the rate of repeat donors should be increased.…”
Section: Introductionmentioning
confidence: 99%